Photoinduced formation of stable Ag-nanoparticles from a ternary ligand-DNA-Ag+ complex12. Issue 12 (28th March 2015) - Berdnikova, Daria V.; Ihmels, Heiko; Schönherr, Holger; Steuber, Marc; Wesner, Daniel
<x xml:space="preserve">Abstract</x> The irradiation of a ternary complex between an intercalator crown-ether conjugate, double-stranded DNA, and Ag+ ions leads to the formation of stable Ag nanoparticles.